Analisis Banjir Di Kawasan Jondul Rawang Kota Padang - Beno Putra Susanto; Dyen Triana Putri; Zahrul Umar -; Aguskamar - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2020)
Flood has been an endless disaster for human being all over the world since the past, nowadays and in future. Water flood may be affected by nature or human activities or even by both nature and human. Almost all region in Indonesia facing the flood problem with various scale and time.Jondul Rawang one place located in south side of Padang city for example is always suffer with water flood. This study is an analysis of flood for Jondul Rawang, using EPA SWMM 5.1 software with simulation method. The simulation result will show location of points on drainage system which start to offer flowincluding the time and duration. Calculation is made based on collected data, hydrology and hydraulyc analysis.The data should cover primary and secondary drainage system then come out with design flood and hydraulyc analysis to check the capacity of drainage.Calculation of rainfall for repeat period using probability method Chi-Kuadratand Smirnov-Kolmogorof will obtain Log Normal Method for rainfall 251,62 mm. To calculate water debit inside drainage for 5 years period flood exist channel 1-2, 3-4, 5-6, and 8-9 with respective overflow 4,5 m3/sec, 6,53 m3/sec, 6,36 m3/sec, and 6,50 m3/sec. While capacity of respective existing drainage are lower such as: 4,47 m3/sec, 5,48 m3/sec, 2,96 m3/sec, and 1,82 m3/sec. Solution to be taken place to resolve the flood problem for Jondul Rawang are Enlarge the drainage size, build retention pond and build infiltration pond.